MUNICIPAL INSURANCE: SOLUSI ALTERNATIF MANAJEMEN RISIKO UNTUK PEMERINTAH DAERAH - Boyke R. Purnomo (Journal of Indonesian Economy and Business (JIEB), 2005)
This paper attempts to analyze the development of municipal insurance in Indonesia.Due to the decentralization implementation in Indonesia which started in 1999, localgovernments are encouraged to be self-managing entity. Beside focus their effort onleveraging the revenue and economic growth, local governments should also take a serious attention on managing their asset’s risk. Municipal insurance is one of the riskmanagement tools used to prevent the decreasing of economic value of local government’s assets. Municipal insurance covers the risk of local government’s infrastructure by proposing a tailor-made insurance contract. The urgency of municipal insurance implementation is become clearer by increasing the frequency and severity of losses affected by many catastrophic risks in Indonesia on last there years. Municipal insurance provides benefit to local government, insurance company, insurance industry, nation and local community.Key words: municipal insurance, risk, risk management, decentralization